Behind High Community Participation: Communication Strategies of Organizers in Socializing Local Head Elections - Nibrosu Rohid (LPPM Stikosa - AWS, 2026)
This study analyzes the communication strategies of the Komisi Pemilihan Umum (KPU Rembang) in enhancing public participation during the Regional Head Election. Using a qualitative descriptive approach, data were collected through interviews, field observations, and document analysis, then examined using thematic analysis to identify key patterns in KPU’s communication practices. The findings reveal that KPU Rembang’s communication strategy is integrated, adaptive, and participatory. The institution combines traditional communication channels such as face-to-face meetings, local radio, and community gatherings with digital media through active use of Instagram, Facebook, and YouTube platforms. The messages are tailored to different audience segments, including young voters, women, rural communities, and persons with disabilities, supported by local opinion leaders and volunteer networks who act as trusted intermediaries between the commission and the public. Despite these successes, several challenges persist, including limited digital infrastructure in rural areas, low digital literacy among older populations, and the spread of misinformation during the election period. KPU Rembang responded by implementing community-based communication resilience, strengthening internal coordination, and maintaining strategic message consistency. The study concludes that public communication serves not only as an informational tool but also as a democratic infrastructure that fosters trust, political literacy, and civic ownership of the electoral process. The results contribute to the broader discourse on political communication in Indonesia and offer practical insights for election management bodies seeking to design inclusive and trust-based public communication strategies.